Epitope-based vaccine design yields fusion peptide-directed antibodies that neutralize diverse strains of HIV-1. (June 2018) - Xu, Kai; Acharya, Priyamvada; Kong, Rui; Cheng, Cheng; Chuang, Gwo-Yu; Liu, Kevin; Louder, Mark; O'Dell, Sijy; Rawi, Reda; Sastry, Mallika; Shen, Chen-Hsiang; Zhang, Baoshan; et al.
Abstract A central goal of HIV-1 vaccine research is the elicitation of antibodies capable of neutralizing diverse primary isolates of HIV-1. Here we show that focusing the immune response to exposed N-terminal residues of the fusion peptide, a critical component of the viral entry machinery and the epitope of antibodies elicited by HIV-1 infection, through immunization with fusion peptide-coupled carriers and prefusion stabilized envelope trimers, induces cross-clade neutralizing responses. In mice, these immunogens elicited monoclonal antibodies capable of neutralizing up to 31% of a cross-clade panel of 208 HIV-1 strains. Crystal and cryoelectron microscopy structures of these antibodies revealed fusion peptide conformational diversity as a molecular explanation for the cross-clade neutralization. Immunization of guinea pigs and rhesus macaques induced similarly broad fusion peptide-directed neutralizing responses, suggesting translatability. The N terminus of the HIV-1 fusion peptide is thus a promising target of vaccine efforts aimed at eliciting broadly neutralizing antibodies. An alternative HIV vaccine design facilitates generation of HIV-1-antibodies, with promising neutralization breadth in rodents and nonhuman primates.